Experimental study on the influence of aerated gas pressure and confining pressure on low-rank coal gas adsorption process. Issue 1 (January 2022) - Yang, Ming; Jia, Gaini; Gao, Jianliang; Liu, Jiajia; Zhang, Xuebo; Lu, Fangchao; Liu, Lei; Pathak, Asmita
To deeply study the variation characteristics of the gas content in the process of gas adsorption for coal samples under different gas pressures and confining pressures, low-field nuclear magnetic resonance technology was used to carry out experimental research on the gas adsorption of coal. The relationship between the T 2 spectrum amplitude integral and the gas quantity was analyzed. The results show the following: (1) When the samples were inflated for 11 h at each gas pressure point (0.31, 0.74, 1.11, and 1.46 MPa), after ∼5 h of adsorption, the amount of adsorbed gas exceeded 85.0% of the total adsorption capacity; additionally, as the adsorption time increased, the amount of adsorbed gas gradually tended to stabilize. When the gas pressure was >1 MPa, the amount of adsorbed gas exceeded 90.0% of the total adsorption capacity; Higher the pressure of aerated gas, greater the gas pressure gradient or concentration gradient on the surface of the coal sample and the greater the driving force for gas molecules to seep or diffuse into the coal sample. (2) When the samples were inflated for 11 h at each confining pressure point (3, 4, 5, and 7 MPa), the adsorbed gas increased by ∼85.0% of the total adsorbed gas in the first 5 h. When the pressure was <5 MPa, the amount of adsorbed gas exceeded 85.0% of the total amount of adsorption; that is, the increase in adsorbed gas was the largest at ∼5 h in the adsorption process for the columnar coal sample under different confining pressures, and the increase was ∼5.0% from 7–11 h. When the large pores in the coal sample closed, the amount of gas that seeped into the deep part of the coal sample within the same aeration time was reduced.